2021
DOI: 10.7759/cureus.17512
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux Disease-Associated Chronic Cough: A Population-Based Analysis of Patient Presentations in the United States

Abstract: Gastroesophageal reflux disease is an extremely prevalent illness in the United States; however, clinicians report that its association with chronic cough is often overlooked and undiagnosed. We used the CERNER Health Facts ® database to analyze the statistical prevalence. Our findings indicate that there is a minority of patients who are untreated for this common complaint. We propose considering this on the differential diagnosis and following current treatment guidelines with proton p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
1
0
2
Order By: Relevance
“…However, there is currently a lack of adequate evidence to support the use of empiric PPI therapy in patients who solely experience LPR symptoms (54). Several uncontrolled studies have indicated that treating chronic cough with antacids can lead to improvement (55). However, recent randomized controlled trial (56) has demonstrated no discernible distinctions between proton pump inhibitors (PPIs) and a placebo in terms of their effectiveness.…”
Section: Proton Pumps Inhibitors (Ppis)mentioning
confidence: 99%
“…However, there is currently a lack of adequate evidence to support the use of empiric PPI therapy in patients who solely experience LPR symptoms (54). Several uncontrolled studies have indicated that treating chronic cough with antacids can lead to improvement (55). However, recent randomized controlled trial (56) has demonstrated no discernible distinctions between proton pump inhibitors (PPIs) and a placebo in terms of their effectiveness.…”
Section: Proton Pumps Inhibitors (Ppis)mentioning
confidence: 99%
“…Однако установление четкой причинно-следственной связи между ГЭРБ и сопутствующими респираторными заболеваниями является сложной задачей в повседневной практике [23]. Помимо изжоги и регургитации существуют внепищеводные проявления ГЭРБ, которые включают БА, хроническую обструктивную болезнь лёгких, хронический кашель [24,25,26], ЛФР, ларингит и синусит, дентальные эрозии [25,27,28,29]. Эти атипичные проявления ГЭРБ, являясь объектом пристального внимания ученых и клиницистов, часто ставят диагностические и терапевтические проблемы и могут потребовать мультидисциплинарного подхода [20,30].…”
Section: распространенность гастроэзофагеальной рефлюксной болезни и ...unclassified
“…Патофізіологічна роль Герх у прояві хронічного кашлю пов'язана з двома переважаючими механізмами: блукаючим стравохідно-трахеобронхіальним рефлюксом і мікроаспірацією вмісту шлунка [22].…”
Section: результати дослідженняunclassified